1997
DOI: 10.2337/diab.46.8.1247
|View full text |Cite
|
Sign up to set email alerts
|

Scientific and Political Impediments to Successful Islet Transplantation

Abstract: Islet transplantation is a treatment for diabetes that has the potential to normalize glucose levels and prevent the development of complications. In spite of the simplicity of the concept and the urgent need to provide such a treatment to patients, there has been a frustrating lack of progress. This perspective delves into the scientific and political impediments to success. The scientific barriers are the need to find a satisfactory source of insulin-producing tissue and the requirement to prevent this tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(59 citation statements)
references
References 78 publications
1
56
1
1
Order By: Relevance
“…[25][26][27][28] By high levels of insulin, hepatocytes may accumulate a high amount of glycogen, but we did not observe overstorage of glycogen in hepatocytes infected with a high MOI number of the adenovirus vector. In insulin gene transfer studies targeted to hepatocytes so far, insulin secretion is constitutive, without any regulation.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…[25][26][27][28] By high levels of insulin, hepatocytes may accumulate a high amount of glycogen, but we did not observe overstorage of glycogen in hepatocytes infected with a high MOI number of the adenovirus vector. In insulin gene transfer studies targeted to hepatocytes so far, insulin secretion is constitutive, without any regulation.…”
Section: Discussioncontrasting
confidence: 61%
“…The liver has been used as an anchoring place for pancreatic islet transplantation. 25 Although Weir and Bonner-Weir 26 reported the poor success of islet transplantation that had been performed intrahepatically through the portal vein in 270 IDDM patients until 1995, there have been several successful cases that became insulin independent. Recently, Carroll et al 27 reported an over 3-year insulin dependence in a patient with intrahepatic islet transplantation.…”
Section: Correspondence: T Takeuchi Department Of Molecular Medicinementioning
confidence: 99%
“…To define strategies to preserve functional islet mass, it is essential to identify the mechanisms of &cell destruction and protection. Isolated human pancreatic islets are susceptible to myriad insults that occur during donor brain-death, organ procurement and preservation, isolation and transplantation [2,31. Although multiple mechanisms are involved in the reduction of functional islet mass, the common pathophysiological process is the trigger of the apoptotic machinery of p-cells.…”
Section: Apoptosismentioning
confidence: 99%
“…The Edmonton Protocol used freshly isolated islets for transplantation [2]. In most former, less successful islet transplant protocols, cultured islets have been used for transplantation, since in vitro culture is often practical from a logistic point of view [4] and may reduce islet immunogenicity by depletion of viable haematogenous and lymphoid cells [5]. Concerns have also been raised regarding the common pronounced exocrine contamination of freshly isolated islet transplants [6].…”
Section: Introductionmentioning
confidence: 99%